If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + -4 = 9x + 50 Reorder the terms: -4 + 11x = 9x + 50 Reorder the terms: -4 + 11x = 50 + 9x Solving -4 + 11x = 50 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -4 + 11x + -9x = 50 + 9x + -9x Combine like terms: 11x + -9x = 2x -4 + 2x = 50 + 9x + -9x Combine like terms: 9x + -9x = 0 -4 + 2x = 50 + 0 -4 + 2x = 50 Add '4' to each side of the equation. -4 + 4 + 2x = 50 + 4 Combine like terms: -4 + 4 = 0 0 + 2x = 50 + 4 2x = 50 + 4 Combine like terms: 50 + 4 = 54 2x = 54 Divide each side by '2'. x = 27 Simplifying x = 27
| 5t+2t-6=24-9 | | 99-6x=12x+23 | | 5z+3=15z | | 8(4a-7)=-56 | | 3(10+15(.8)+2)= | | 5(2a+3)=65 | | 2(3+5x+-2x^2)=0 | | 5-9x=59-23x | | 105x=80*95 | | 3(10+15d+2)= | | 3(4-s)-5s=52 | | 103x=80*95 | | 5h+11=2h+35 | | 8=-.4x+4 | | 31+2=-1-2 | | 4y=6x-48 | | .7-.5x=1.2x-2.7 | | 2p/6-23=-15 | | .2-.3=.4-.5y | | 9k=5k+32 | | 4x-6=6x-8 | | .3x+1.38=.24x+1.2 | | 5k-20=-2+8k | | xy-3y=40 | | 4x-6=6x+8 | | 7p/9-43/9=-4 | | 8x^2+24x-32=0 | | 4x+6=6x-8 | | .2x+.5=.7x-4 | | 3x-2(1.5x+1)=6x-2(3x+9) | | 7b=4b+27 | | .29x-.25=.43x+.03 |